Pengaruh Fraksi Volume dan Orientasi Serat Pada Komposit Hibrid Berpenguat Serat Gambas serta Eceng Gondok Terhadap Kekuatan Bending - Rizki Ramadoni; firdaus firdaus; Romli Romli; Sailon Sailon; A. Pramudya AFG; Muhammad Nugraha (Jurnal Teknik Mesin, 2022)
Wood is increasingly difficult to obtain due to the use of excess wood. Many efforts were made to replace wood, one of which was composite material. This study aims to determine the most optimal bending strength with the influence of variations in volume fractions and fiber orientation in hybrid composites with luffa fibers and hyacinth fibers. In making composites using the hand lay-up method with alaklization treatment on gambas and hyacinth fibers using 5% NaOH which is varied with the volume fraction used in this study with the ratio of resin: hyacinth: gambas is (60%:20% :20%),(70%:15%:15%), as well as (80% :10%:10%) and the orientation of the fibers with the arrangement of the luffa / hyacinth / luffa layer is (0°/ 45 °/ 90°), (0˚/45˚/0˚), (90˚/0˚/90˚). Bending testing was performed with ASTM D790 standard and hypothesis testing using the two-way ANOVA method. From the results of bending testing, the most optimal strength value was found, which was 43.33 N / mm2, where the value was not higher than the bending strength value in the multiplex, which was 17.53 N / mm2. Meanwhile, the results of hypothesis testing are that there is an influence on the volume fraction factor, the direction of fiber orientation and the interaction with bending forces.